2007
DOI: 10.1177/0734371x07307149
|View full text |Cite
|
Sign up to set email alerts
|

Does Person-Organization Fit Mediate the Relationship Between Public Service Motivation and the Job Performance of Public Employees?

Abstract: Public service motivation (PSM) is argued to be a meaningful predictor of the performance of employees in public organizations. Many scholars predict that as the level of PSM increases, the performance of public employees will also increase. Unfortunately, existing research has yet to fully support this hypothesis. Two published studies that tested this hypothesis have come to different conclusions. This study investigated whether Person—Organization Fit (P—O Fit) mediates the relationship between PSM and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
382
6
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(427 citation statements)
references
References 22 publications
15
382
6
11
Order By: Relevance
“…13, No. 9;2018 The findings of the study support the hypothesis that SCO has a significant effect on SB (β=0.59,R²=0.43 and F=18.50). Studies on the subject have shown that employees with a high level of SCO develop more compliance behavior towards safety rules, policies and procedures (Wallace & Vodanavich, 2003;Clarke & Robertson, 2005;Inness et al, 2010).…”
Section: The Effects Of Pof and Sco On Sc And Sbsupporting
confidence: 77%
See 3 more Smart Citations
“…13, No. 9;2018 The findings of the study support the hypothesis that SCO has a significant effect on SB (β=0.59,R²=0.43 and F=18.50). Studies on the subject have shown that employees with a high level of SCO develop more compliance behavior towards safety rules, policies and procedures (Wallace & Vodanavich, 2003;Clarke & Robertson, 2005;Inness et al, 2010).…”
Section: The Effects Of Pof and Sco On Sc And Sbsupporting
confidence: 77%
“…The conflict between employee values and demands with organizational values and norms will also affect the employee's judgments on all rules and procedures. Weak POF has negative effects on the work outcomes such as job satisfaction, intention to leave work and performance (Kristof, 1996;Bright, 2007;Cable & Judge, 1996;Vilela et al, 2008). Weak POF has also the potential to explain poor safety behavior.…”
Section: The Effects Of Pof and Sco On Sc And Sbmentioning
confidence: 99%
See 2 more Smart Citations
“…Referring back to Ellie and Russell, it looks as if Ellie is experiencing a good person-environment fit: she feels able to respond to her own need to contribute to society, with the likely result that she will perform well. Russell, on the other hand, is experiencing a misfit: he is highly motivated to contribute to society but feels unable to do so -his needs are not being met by his working environment, blocking his drive to contribute to society and, as a result, to perform highly.Studies have used person-environment fit theory in an attempt to understand the role of context for the relationship between PSM and work outcomes (Bright 2007; GouldWilliams et al 2013;Leisink & Steijn 2009;Steijn 2008;Taylor 2008;. In general they found that a fit matters.…”
mentioning
confidence: 99%